Taxonomic revision of the Deltohyboma Lane, 1946 gilli species group (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilum) - González-Alvarado, Arturo; Vaz-de-Mello, Fernando Z. (European Journal of Taxonomy, 2021)
The dung beetles belonging to the genus Deltochilum Eschscholtz, 1822 are widely distributed in the Neotropical region. This genus is divided into eight subgenera, of these, the subgenus Deltohyboma Lane, 1946 is the most diverse, with an estimated 212 species. The most recent revision of Deltohyboma divided the subgenus into 19 species group. Here, taxonomy of the gilli species group is revised. Four new species (D. jocelynae sp. nov., D. nonstriatum sp. nov., D. quasistriatum sp. nov. and D. tenuistriatum sp. nov.) are described, making a total of five species within the species group. Keys for species identification and habitus as well as male genitalia morphology are illustrated.